Hotel Transylvania. Transformania [videorecording (Blu-Ray)] - Vernon, Amos; Randazzo, Nunzio; Tartakovsky, Genndy, 1970- (Sony Pictures Home Entertainment, 2023)
After one experiment, Johnny turns into a monster and everyone else becomes human. Now it has to be seen whether they will be able to reverse this experiment.